STRUCTURE OF THE TESTES OF WHITE OUTBRED RATS - Yodgorov I.F.; Baymuradov R.R. (Central Asian Journal of Medical and Natural Science, 2023)
Testes are sensitive organs to various pathologies, therefore histopathological examination of testes is important in assessing spermatogenesis and testicular function, both in clinical practice and laboratory experiments. The article provides information about the normal structure of the testes in white rats at puberty.